Displacement Forces in Stent Grafts: Influence of Diameter Variation and Curvature Asymmetry. Issue 2 (August 2016) - Roos, H.; Tokarev, M.; Chernoray, V.; Ghaffari, M.; Falkenberg, M.; Jeppsson, A.; Nilsson, H.
Abstract : Objectives: Long-term durability after endovascular aortic repair is influenced by stent graft migration causing types I and III endoleaks. Flow induced displacement forces have been shown to have the potential to cause migration. In this study, the influence of the distal diameter of iliac limb stent grafts and the shape of graft curvature on flow induced displacement forces, were investigated. Methods: In an experimental pulsatile flow model mimicking aortic conditions in vivo, flow induced displacement forces at the proximal and distal ends of iliac limb stent grafts were studied at different angles (0–90°) and perfusion pressures (145/80, 170/90, 195/100 mmHg). Bell-bottomed, tapered, and non-tapered stent grafts and also asymmetric stent graft curvatures at 90° bend were studied. Measurements of graft movement were performed at all studied angulations and graft shapes. Results: For all stent graft diameters, flow induced displacement forces increased with higher pressure and increased stent graft angulation. Forces in the bell-bottom graft were considerably higher than in tapered and non-tapered grafts, with a markedly elevated peak force at the distal end (proximal end, 2.3 ± 0.06 N and distal end, 6.9 ± 0.05 N compared with 1.7 ± 0.08 N and 1.6 ± 0.08 N in non-tapered grafts; p  < .001 both). Peak forces in tapered and non-tapered grafts were not significantly different between the proximal and distal end. In asymmetric stent graft curvatures, a significant increase in displacement forces was observed in the attachment zone that was closest to the stent graft bend. Graft movement increased with greater displacement forces. Conclusion: Flow induced displacement forces in iliac limb stent grafts are significant and are influenced by distal stent graft diameter and the shape of the graft curvature. The displacement forces are particularly high at the large distal end of bell-bottom grafts. Wide iliac arteries treated with bell-bottom stent grafts may require more vigilant surveillance and improved stent graft fixation.